Sistem Rekomendasi Produk Indibiz Menggunakan Metode Knowledge Base - Rendhiva, Lidia; Dwi Hartanti; Evi Yuliana , Margaretha (LPPM Politeknik Aceh Selatan, 2024)
Many companies in the electronic field are competing in the business sector. One of them is PT Telekomunikasi Indonesia Klaten branch which sells Indibiz products. Indibiz products are internet products designed for Small and Medium Enterprises. The variety of internet products available makes customers face difficulties in choosing internet products. Because of these problems, it is important to develop a recommendation system that can help customers. The researcher's goal is to design a recommendation system using the Knowledge Base method for internet product selection. Researchers use the Knowledge Base Recommendation method which has the advantage of being able to set a priority scale according to customer needs. Researchers also carry out a system development method using Rapid Application Development (RAD) which consists of 3 stages, namely business modeling, data modeling, and process modeling. In this modeling, internet product selection includes 4 search attributes, namely internet type, price, facilities, and internet speed. Based on the results of calculating the similarity value with 42 sample data, the system can provide internet product recommendations that match customer needs based on attributes. Internet products with the highest similarity value of 0.769 will be displayed in the recommendation system. With the design of this system, it can make it easier for customers to determine the selection of internet products needed.